2022
DOI: 10.2147/copd.s338436
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of New Users of Single- and Multiple-Inhaler Triple Therapy for COPD in Primary Care in England

Abstract: Purpose Inhaled triple therapy is recommended for patients with chronic obstructive pulmonary disease (COPD) who have poorly controlled symptoms and to reduce the risk of exacerbations. This study assessed the clinical characteristics of new users of single- and multiple-inhaler triple therapy (SITT and MITT) treated in a primary care setting in England. Patients and Methods This cross-sectional, observational study used data from an electronic health record database (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…A cross-sectional observational study of COPD patients attending primary care in England including 3536 new users of single-inhaler triple therapy reported similar levels of breathlessness, lung function impairment and treatment history among those prescribed triple therapy; 65% of patients had an MRC dyspnea score ≥3, 45% had predicted FEV 1 <50%, and 46%, 25% and 12% of patients had previously received multiple inhaler triple therapy, ICS/LABA or LABA/LAMA therapy, respectively, prior to triple therapy prescription. 31 Like our study, many patients appeared to have asthma in addition to…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…A cross-sectional observational study of COPD patients attending primary care in England including 3536 new users of single-inhaler triple therapy reported similar levels of breathlessness, lung function impairment and treatment history among those prescribed triple therapy; 65% of patients had an MRC dyspnea score ≥3, 45% had predicted FEV 1 <50%, and 46%, 25% and 12% of patients had previously received multiple inhaler triple therapy, ICS/LABA or LABA/LAMA therapy, respectively, prior to triple therapy prescription. 31 Like our study, many patients appeared to have asthma in addition to…”
Section: Discussionsupporting
confidence: 54%
“… 31 Like our study, many patients appeared to have asthma in addition to COPD, which may have been the reason for initiation of an ICS-containing therapy (25% with current asthma compared to 30.9% in our study). 31 …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…7 Recent studies conducted in the UK, the US, and Japan have assessed characteristics of patients initiating MITT and SITT (Akiyama S, et al Characteristics of new users of single-and multiple-inhaler triple therapy for COPD in routine clinical practice in Japan: a cross-sectional, observational study [unpublished data]). [14][15][16] Data from the UK and the US suggest that MITT and SITT are frequently initiated following prior maintenance therapy, and in patients with a recent exacerbation, in line with current clinical guidance. [14][15][16] However, data from a similar retrospective cohort study conducted in Japan reported that 25% of patients initiating triple therapy had no prior history of ICS, LABA, or LAMA in the past 12 months (Akiyama S, et al Characteristics of new users of single-and multiple-inhaler triple therapy for COPD in routine clinical practice in Japan: a crosssectional, observational study [unpublished data]).…”
Section: Introductionmentioning
confidence: 60%
“…Switching from MITT to SITT is common in the UK. 18 Patients may switch for clinical reasons (eg, following an exacerbation), but also for economic reasons. Compared with MITT, SITT with FF/UMEC/VI has been shown to be a cost-effective treatment option for symptomatic patients with COPD who have a history of one or more exacerbations in a UK setting.…”
Section: Discussionmentioning
confidence: 99%